Drug repurposing and cytokine management in response to COVID-19: a re- view (2020)
Coronavirus disease 2019 (COVID-19), the infectious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an aggressive disease that attacks the respiratory tract and has a higher fatality rate than seasonal influenza. The COVID‐19 pandemic is a global health crisis, and no specific therapy or drug has been formally recommended for use against SARS-CoV-2 infection. In this context, it is a rational strategy to investigate the repurposing of existing drugs to use in the treatment of COVID-19 patients. In the meantime, the medical community is trialing several therapies that target various antiviral and immunomodulating mechanisms to use against the infection. There is no doubt that antiviral and supportive treatments are important in the treatment of COVID-19 patients, but anti-inflammatory therapy also plays a pivotal role in the management COVID-19 patients due to its ability to prevent further injury and organ damage or failure. In this review, we identified drugs that could modulate cytokines levels and play a part in the management of COVID-19. Several drugs that possess an anti-inflammatory profile in others illnesses have been studied in respect of their potential utility in the treatment of the hyperinflammation induced by SAR-COV-2 infection. We highlight a number of antivirals, anti-rheumatic, antiinflammatory, antineoplastic and antiparasitic drugs that have been found to mitigate cytokine production and consequently attenuate the “cytokine storm” induced by SARS-CoV-2. Reduced hyperinflammation can attenuate multiple organ failure, and even reduce the mortality associated with severe COVID-19. In this context, despite their current unproven clinical efficacy in relation to the current pandemic, the repurposing of drugs with anti-inflammatory activity to use in the treatment of COVID-19 has become a topic of great interest.